2015
DOI: 10.1093/neuonc/nov043
|View full text |Cite
|
Sign up to set email alerts
|

Does lung cancer mutation status and targeted therapy predict for outcomes and local control in the setting of brain metastases treated with radiation?

Abstract: This study suggests that EGFR tyrosine kinase mutation and ALK translocation results in improved survival to targeted therapies and that mutation status itself does not predict survival and local control in patients with brain metastases from NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…23,24 Two large series evaluating the efficacy of SRS in the treatment of EGFR-mutant brain metastases reported local control rates of 100% and 93%. 23,25 In addition to the potential for SRS to improve OS compared with WBRT, numerous studies have demonstrated that SRS has less acute and late toxicity. [26][27][28] Given the prolonged survival of patients with EGFR-mutant NSCLC, the use of SRS to defer (or completely avoid) the neurocognitive sequelae of WBRT is of particular importance.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Two large series evaluating the efficacy of SRS in the treatment of EGFR-mutant brain metastases reported local control rates of 100% and 93%. 23,25 In addition to the potential for SRS to improve OS compared with WBRT, numerous studies have demonstrated that SRS has less acute and late toxicity. [26][27][28] Given the prolonged survival of patients with EGFR-mutant NSCLC, the use of SRS to defer (or completely avoid) the neurocognitive sequelae of WBRT is of particular importance.…”
Section: Discussionmentioning
confidence: 99%
“…22,[29][30][31][32][33][34] The majority of studies to date, however, included patients who received prior WBRT, which confounds the pattern of intracranial failure and makes the results difficult to interpret. 22,[29][30][31][32][33][34] The majority of studies to date, however, included patients who received prior WBRT, which confounds the pattern of intracranial failure and makes the results difficult to interpret.…”
Section: -5 --mentioning
confidence: 99%
“…Prior studies have reported mixed rates of DBF for patients with EGFR, ALK, and KRAS mutations. 22,[29][30][31][32][33][34] The majority of studies to date, however, included patients who received prior WBRT, which confounds the pattern of intracranial failure and makes the results difficult to interpret. Johung et al analyzed 81 patients with NSCLC-AC BMs, 32% of whom had received prior WBRT, and reported EGFR mutation status was not associated with an increased risk of DBF (P = .67).…”
Section: -5 --mentioning
confidence: 99%
“…[81] In a retrospective study of 89 patients with NSCLC treated with stereotactic radiation therapy for CNS metastases, the addition of targeted therapies was associated with significantly better outcomes. Patients treated with targeted therapy against EGFR or ALK had a median survival of 21 months compared with 11 months for patients who did not receive targeted therapy.…”
Section: Breast Cancermentioning
confidence: 99%
“…Patients treated with targeted therapy against EGFR or ALK had a median survival of 21 months compared with 11 months for patients who did not receive targeted therapy. [81] EGFR mutations are present in 10-25% of NSCLC. EGFR mutations in patients with brain metastases may be more common; two reports found EGFR mutations to be present in 63% and 50% of patients, raising the question whether EGFR mutations lead to an increased risk of developing brain metastases similar to HER2 overexpression in breast cancer.…”
Section: Breast Cancermentioning
confidence: 99%